Dead Sea pollen provides new insights into the paleoenvironment of the southern Levant during MIS 6–5. (15th May 2018) - Chen, Chunzhu; Litt, Thomas
Abstract: The paleoclimate of the southern Levant, especially during the last interglacial (LIG), is still under debate. Reliable paleovegetation information for this period, as independent evidence to the paleoenvironment, was still missing. In this study, we present a high-resolution pollen record encompassing 147–89 ka from the Dead Sea deep drilling core 5017-1A. The sediment profile is marked by alternations of laminated marl deposits and thick massive halite, indicating lake-level fluctuations. The pollen record suggests that steppe and desert components predominated in the Dead Sea surroundings during the whole investigated interval. The late penultimate glacial (147.3–130.9 ka) and early last glacial (115.5–89.1 ka) were cool and relatively dry, with sub-humid conditions confined to the mountains that sustained moderate amounts of deciduous oaks. Prior to the LIG optimum, a prevalence of desert components and a concomitant increase in frost-sensitive pistachio trees demonstrate the occurrence of an arid initial warming phase (130.9–124.2 ka). The LIG optimum (124.2 ka–115.5 ka) was initiated by an abrupt grass expansion that was followed by a rapid spread of woodlands in the mountains due to increased moisture availability. The remarkable sclerophyllous expansion points to a strong seasonal moisture deficit. These results contradict previous Dead Sea lake-level investigations that suggested pluvial glacials and a warm, dry LIG in the southern Levant. Prominent discrepancies between vegetation and Dead Sea lake stands are also registered at 128–115 ka, and the potential causes are discussed. In particular, while the pollen spectra mirror increased effective moisture during the LIG optimum, the massive halite deposition is indicative of an extremely low lake level. Given that the climate amelioration triggered the migration of early modern humans to the southern Levant, we speculate that the diverse ecosystems in the region provided great potential for their residence. Across the eastern Mediterranean region, an analogous vegetation succession pattern is observed. Highlights: First high-resolution pollen & charcoal record from the last interglacial Dead Sea. Arboreal and sclerophyllous expansion during the last interglacial optimum. Discrepancies between the Levantine vegetation and Dead Sea lake level. Diverse ecosystems in the southern Levant for the residence of early modern humans.